2015
DOI: 10.1177/2158244015612877
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and Post-Stroke Experiences of Working-Age Survivors During Recovery

Abstract: Survivors who experience stroke of mild to moderate severity are typically discharged home quickly, with only minimal referral for rehabilitation follow-up or support to meet specific needs in recovery. Particular vulnerabilities of younger, higher functioning stroke survivors have received some recognition in international literature in recent years. This article reports on findings of a small Australian qualitative study focusing on recovery and return to work experiences of young higher functioning female s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 46 publications
(60 reference statements)
0
36
0
Order By: Relevance
“…The impact of the stroke event will depend on the location, extent and severity of the damage in the brain both in the short term and long term but the overall impact on individuals can be devastating (Crichton et al, 2016). The degree of recovery or damage and the associated timescales will vary widely between individuals and can affect all aspects of life (physical, cognitive and behavioural) as well as the ability to take part in social, family and work activities (McKevitt et al, 2011;Murray & Harrison, 2004;Wolfenden & Grace, 2015). While stroke is more common in older populations, younger adults tend to have lower mortality rates meaning that recovery for this group is more likely and rehabilitation is of critical importance (Feigin et al, 2017;Martinsen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the stroke event will depend on the location, extent and severity of the damage in the brain both in the short term and long term but the overall impact on individuals can be devastating (Crichton et al, 2016). The degree of recovery or damage and the associated timescales will vary widely between individuals and can affect all aspects of life (physical, cognitive and behavioural) as well as the ability to take part in social, family and work activities (McKevitt et al, 2011;Murray & Harrison, 2004;Wolfenden & Grace, 2015). While stroke is more common in older populations, younger adults tend to have lower mortality rates meaning that recovery for this group is more likely and rehabilitation is of critical importance (Feigin et al, 2017;Martinsen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the young survivors with aphasia who returned to work (Kuluski et al, ; Wolfenden & Grace, ), those who returned to school were also concerned about impaired language performance, reporting reduced linguistic self‐confidence. Furthermore, most participants presented symptoms of anxiety, which may be connected to their views on language considering the high correlation between worries about language performance and actual symptoms (see also Cahana‐Amitay et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies (e.g., Kuluski, Dow, Locock, Lyons, & Lasserson, ; Wolfenden & Grace, ) have predominantly focused on stroke survivors' return to the workplace, there seems to be insufficient research regarding this phenomenon in a classroom context. Not only is inquiry on the subject of college student stroke survivors lacking, but studies on college aphasic students in particular are non‐existent.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of a work role may further influence and possibly decrease social networks and reduce life satisfaction (Daniel et al., 2009; Vestling et al., 2003; Wolfenden & Grace, 2015). This tendency was also present in this study where the social networks were reported to be reduced 20%–70% at 6–12 months post discharge.…”
Section: Discussionmentioning
confidence: 99%